Evaluation of Prosopis pods as a source of carbohydrate for enhancing the growth of soilborne fungi - and L.N. HARSH, SATISH LODHA, M.D. BOHRA (Indian Phytopathology, 2002)
The potential of Prosopis juliflora pods in promoting fungal growth in culture media by replacing the chemical or other source of sugar was studied. Supplementing decoction of Prosopis pods at different rates in potato agar medium significantly enhanced the mycelial growth and sporulation of Macrophomina phaseolina, Fusarium solani, Fusarium oxysporum f.sp. cumini and Trichoderma harzianum, compared to PDA and Richards agar media. The fastest growth was recorded in T. harzianum and M. phaseolina, where the mycelial mats covered the Petri dishes in 45 and 51 h, respectively, on PPA (Prosopis pod-potato agar) containing 13.7 g sugar. In liquid culture, dry mycelial weights of M. phaseolina, F. solani, F. oxysporum f. sp. cumini and T. harzianum weresignificantly higher on Prosopis pod broth (PPB) compared to potato dextrose broth (PDB) and Richards media. Higher number of colony forming units of all the 4 fungi were also recorded on Prosopis pod:sand medium as compared to maize meal: sand medium.